Pendampingan Penerapan Metode Tuntas Dalam Menghafal Juz Amma di Rumah Tahfizh Al-Muayyad Gumawang - Kholidin, Nor (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2020)
Common problems that often arise in the program to memorize the Qur'an for children include children who memorize but cannot read or can memorize but cannot write. Factors that influence the success of the program to memorize the Qur'an include internal factors of students and external factors such as teacher competence and methods used. Complete method is a method that combines the ability to read, write and memorize the Qur'an. The flow of this service activity is socialization, training, mentoring and evaluation. The results of this service activity have been able to answer the initial goal of service, namely providing education about the Complete method and improving students' reading, writing and memorizing competencies